EFFECTIVITY OF NINTENDO WII AS REHABILITATION THERAPY IN POST STROKE PATIENTS: A SYSTEMATIC REVIEW - Wardani, Rachmawati; Salsabila, Sirin; Rahman, Arizal Novrianto; Rakhmatiar, Rodhiyan (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2021)
Post stroke patients need medical rehabilitation to live an independent life. Nintendo Wii technology presents an alternative choice that is quite safe, feasible, and has a high potential in rehabilitating & restoring motor function in post stroke patients. Although it has been widely used as adjunct therapy in stroke rehabilitation facilities throughout the world, only a few acknowledge its effectivity in post-stroke patients. This study aims to conduct a systematic review in order to identify and assess the results used in evaluating Nintendo Wii technology as rehabilitation therapy for stroke patients. Thus, the study used for this research is systematic review. Materials included in this study are research/studies found in NCBI, PubMed, Cochrane and other relevant online databases. From this research, it is found that Virtual Reality (VR) such as Nintendo Wii considered as an additional rehabilitation therapy that provides a significant improvement in various aspects of exercise therapy, such as; balance; walking ability; statistical and dynamic strengths; motivation as well as socialization; and recovery of physical function in stroke patients. Nintendo Wii can also be used safely in stroke patients and there have been no reports of side effects from this therapy.